PENEMPATAN PEGAWAI DI BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI KALIMANTAN BARAT - Sri Maryati E.21109016 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
This study aims to describe and analyze the apparatus location of Economic Planning Area in Bappeda of West Kalimantan Province. Benefit theoretically as source of information science, specially in development program of Human Resource and Administrative Science State. Practically is expected as opinion contribution for the Bappeda of West Kalimantan Province, due to process the apparatus location of Economic Planning Area according to job analysis. Result of research indicate that still there are among apparatus which low education it, so that have an in with the officer performance, especially job experience covering productivity and skill work, because low involve in education and practice. Therefore, head suggested by more opening of officer opportunity to follow the education and practice. The mentioned needed to a orderliness work, because duty burden given by have down alley owned each apparatus. Keywords:  Apparatus  Location,  Education,  Productivity,  Skill Work  and  Job Experience Apparatus.